MANAJEMEN LIKUIDITAS BANK SYARI’AH (Upaya Peningkatan Good Corporate Governance) - Sulistyowati, Sulistyowati (UNIVERSUM, 2015)
Both of conventional and syari’ah bank have an obligation to reassure the customers that the money they save is secured. Thus, in order to provide security to the customers, the bank should have a liquidity management which forces the bank to meet the current or the future obligation in the event of withdrawal or redemption of liability asset. So it is able to meet its obligations, particularly a short term fund obligation. From the point of asset, liquidity is an ability to change the entire assets into cash. While liability is an ability to meet the financing need through an increase in a portfolio liability.There are some liquidity instruments that can be run by the syari’ah bank in order to meet its obligation, namely: the first is the Statuary Reserve Requirement (SRR). It is a minimum deposit of a commercial bank in a current account as has been stipulated by Bank Indonesia based on a certain percentage of the third party fund; the second is the so called cliring which is understood as an activity which has been going since the time of a transactional agreement to a completion of such agreement (an agreement between financial institution regarding with a payable account in a financial transaction). In order to improve the management of the bank’s fund, namely the advantage and disadvantage of the fund management, it needs the Inter-Bank Money Market. Based on the principles of syari’ah and to manage the advantage and disadvantage of the fund efficiently, it is necessarily in need of the Inter-Bank Money Market which uses the mudharabah investment for inter-bank; the third is the instrument of the wadi’ah certificate of Bank Indonesia which can be used as a means of deposit short-term fund, especially for those that have an excess of liquidity; and the fourth is the syari’ah capital market which has relationship with the offering and trading of the stock exchange, the public companies related to the issuance of the stock exchange, and the institution and profession of the stock exchange in accordance with the syari’ah principles.Keywords : Likuiditas, Manajemen Likuiditas, Instrumen Likuiditas